Descriptive analysis of a 1:1 physiotherapy outpatient intervention post primary lumbar discectomy: one arm of a small-scale parallel randomised controlled trial across two UK sites. Issue 11 (9th November 2016) - Rushton, A; Calcutt, A; Heneghan, N; Heap, A; White, L; Calvert, M; Goodwin, P
Abstract : Objective: There is a lack of high-quality evidence for physiotherapy post lumbar discectomy. Substantial heterogeneity in treatment effects may be explained by variation in quality, administration and components of interventions. An optimised physiotherapy intervention may reduce heterogeneity and improve patient benefit. The objective was to describe, analyse and evaluate an optimised 1:1 physiotherapy outpatient intervention for patients following primary lumbar discectomy, to provide preliminary insights. Design: A descriptive analysis of the intervention embedded within an external pilot and feasibility trial. Setting: Two UK spinal centres. Participants: Participants aged ≥18; post primary, single level, lumbar discectomy were recruited. Intervention: The intervention encompassed education, advice, mobility and core stability exercises, progressive exercise, and encouragement of early return to work/activity. Patients received ≤8 sessions for ≤8 weeks, starting 4 weeks post surgery (baseline). Outcomes: Blinded outcome assessment at baseline and 12 weeks (post intervention) included the Roland Morris Disability Questionnaire. STarT Back data were collected at baseline. Statistical analyses summarised participant characteristics and preplanned descriptive analyses. Thematic analysis grouped related data. Findings: Twenty-two of 29 allocated participants received the intervention. STarT Back categorised n=16 (55%) participants 'not at low risk'. Physiotherapists identified reasons for caution for 8 (36%) participants, commonly risk of overdoing activity (n=4, 18%). There was no relationship between STarT Back and physiotherapists' evaluation of caution. Physiotherapists identified 154 problems (mean (SD) 5.36 (2.63)). Those 'not at low risk', and/or requiring caution presented with more problems, and required more sessions (mean (SD) 3.14 (1.16)). Conclusions: Patients present differently and therefore require tailored interventions. These differences may be identified using clinical reasoning and outcome data. Trial registration number: ISRCTN33808269; post results.